Influences of carbon fillers on electrical conductivity and crystallinity of polyethylene terephthalate - Xin, Fei (2013)
Three forms of carbon, i.e., carbon nanotubes (CNT), conductive carbon black (CCB), and graphite (G), were added to polyethylene terephthalate (PET) to prepare several types of composites, namely, CNT/PET, CCB/PET, G/PET, CNT/CCB/PET, and CNT/G/PET composites, using melt compounding, followed by injection molding. These composites were characterized using field emission scanning electron microscopy, differential scanning calorimetry, and electrical conductivity measurements. It was found that the addition of these conductive fillers could result in the electrically conductive composites directly but the conductivities were dependent on many factors including filler type, content, dispersion state in the matrix, complementary effect of two fillers (i.e., dual fillers), and post melt annealing. Among those carbon/PET composites studied, the highest conductivity that could be reached was 1.2 S/cm, which was 17 orders of magnitude higher than that of the matrix PET. The melt annealing process was found to remarkably enhance the electrical conductivity of carbon/PET composites. CNT, CCB, and G, all could act as nucleating agents but the crystallinity of PET decreased with increasing the filler content in the composites. All types of fillers caused shifting of the crystallization temperature to higher temperatures. The mechanisms for the effects of carbon fillers on electrical conductivity and cystallinity of PET have been proposed and discussed.